LPPM UMSB ISSN 1693-2617 E-ISSN 2528-7613 206 THE PROFESSIONAL DEVELOPMENT OF CERTIFIED KINDERGARTEN TEACHER - Tri Irfa Indrayani, Ramadani (Menara Ilmu, 2018)
Certification is the process of giving certificate for the teacher who have certain requirements,such as academic qualifications, teaching competence, physical and spiritual health, andresponsibility to achieve the national education goals. This research aimed to know: (1) theprofessional development that done by certified kindergarten teacher, (2) the efforts that doneby kindergarten teacher in developing the professionalism, (3) the barriers of kindergartenteachers in developing the professionalism, (4) the efforts to overcome the barriers ofprofessional development. This research used qualitative method. The result of this researchshowed that : (1) certified kindergarten teacher must increase the professionalism, (2) theefforts to develop the professionalism of kindergarten teachers were seminars, workshops,training, KKG and IGTKI (3) the barriers that came from themselves such as lack of time,funds, ability, and willing, the while the barriers that came from institutions such as lack offunds and facilities, (4) the effort to overcome the barriers were using the time well and havingmotivation to study, and the barriers that came from department and institution were solved bycommunication.Keywords: certified teacher, kindergarten teacher professional